Managerial Economic Disciplinary in Strategy Planning - Romprasert, Suppanunta (Asian Administration and Management Review, 2019)
This research is about attitude on planning to study in Economics program for Master Degree. The objectives are to search the important variables affecting on attitude of public, to plan on studying in Master of Managerial Economics, to study public’s expectation toward their attitudes via by fundamental factors and to compare attitude assessment of public to plan on studying in Master Level. Sampling group uses in this paper be the 400 people in public. The data analysis is done by frequency and percentage, mean, standard deviation, t-test, and one-way ANOVA analysis of variance. The outcomes are following as: the most important factor in considering the master degree program in managerial economics is benefits in graduating from the program. The age factor has the impact to the level of attitudes about studying master degree for those who are 30 years old is concentrating in teaching style. However, those who are less than 30 years old give importance to other factors like subjects in the program or the support from professors and coordinators. People who have graduated from finance or economics program in bachelor degree and people who expect to work in finance areas like banking or corporate finance will have high level of intention to study master degree program in managerial economics.